An Evaluation of Baseline Kidney Function in the REPRIEVE Trial of Pitavastatin in Human Immunodeficiency Virus. (9th July 2020) - Overton, Edgar T; Kantor, Amy; Fitch, Kathleen V; Muntner, Paul; Supparatpinyo, Khuanchai; Mosepele, Mosepele; Mohapi, Lerato; Cardoso, Sandra Wagner; Patil, Sandesh; de Lacerda, Marcus V G; McComsey, Grace; Aberg, Judith A; et al.
Abstract: Background: Chronic kidney disease is a common comorbid condition among persons living with human immunodeficiency virus (PWH). We characterized baseline kidney function in the REPRIEVE (Randomized Trial to Prevent Vascular Events in HIV) trial cohort. Methods: REPRIEVE enrolled PWH with low to moderate cardiovascular risk based on traditional risk factors to evaluate the effect of statin therapy on cardiovascular events. We determined baseline estimated glomerular filtration rate (eGFR) with the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI), Modification of Diet in Renal Disease, and Cockcroft-Gault equations, and we evaluated baseline factors associated with eGFR <90 mL/min/1.73 m 2 by logistic regression. We performed Bland-Altman plots and scatterplots to assess agreement between equations. Results: Among 7770 participants enrolled, the median age was 50 years, 31% were female (natal sex), 43% black or African American and 15% Asian, the median body mass index (calculated as calculated as weight in kilograms divided by height in meters squared) was 25.8, and the median CD4 cell count 620/µL. The median CKD-EPI eGFR was 97 mL/min/1.73 m 2, and 38% had an eGFR <90 mL/min/1.73 m 2 . In the adjusted model, factors associated with eGFR <90 mL/min/1.73 m 2 included white race, older age, higher body mass index, high-income region of enrollment, hypertension, and tenofovir disoproxil fumarate. The CKD-EPI and Modification of Diet in Renal Disease equations demonstrated strong agreement, particularly at lower eGFR values. Overall, there was 56% concordance between the 3 equations (categories <60, 60 to <90, ≥90 mL/min), improving to 73% after accounting for individual body surface area. Conclusions: REPRIEVE enrolled a diverse cohort including a substantial number of PWH with reduced kidney function. Factors associated with reduced eGFR included traditional risk factors and tenofovir disoproxil fumarate exposure. Three commonly used equations have only fair agreement, with potential implications for both clinical care and epidemiologic studies. Clinical Trials Registration: NCT02344290.